Claim Reserves Estimation Using Chain Ladder Method in Casualty Insurance for the Period 2010 - 2019 - Muara Lysta Sirait; Muhammad Alfarisi; Zievan Ananta Pahlevi; Maria Yus Trinity Irsan (International Journal of Management and Business Economics, 2024)
In a work environment, the presence of risk or unforeseeable events is inevitable, as employees certainly seek to get a sense of security in doing work. Therefore, insurance is responsibility to provide sense of security to employees by providing protection in the form of claim payments to employees who get accidents. To meet the claim payment, insurance companies need to prepare funds. With the chain ladder method, insurance companies can estimate how much funds must be prepared to make claim payments. This study used the secondary data from general insurance companies in the United States published by the National Association of Insurance Commissioners under the title "Statistical Compilation of Annual Statement Information for Property/Casualty Insurance Companies in 2019". Data in the form of cumulative run-off triangle with accident period 2010-2019. Through this calculation, claim reserves that must be prepared by insurance companies for 2020 amounted to USD 1,553,906.